'A real woman has to do it all – with the kids and in the office': Doing femininity in the transcultural context of Russian-German migration. Issue 6 (2nd June 2016) - Rohde-Abuba, Caterina
Abstract : The au pair stay allows young women to experience the doing gender of family work and waged work in another cultural context than their own. This article investigates how Russian university graduates, who had been working as an au pair in Germany, developed transcultural strategies to balance work and family for their prospective future referring to these different experiences. It will be shown that interviewees rejected the Soviet family model of the fulltime 'working mother'. Some women positively evaluated that in Germany the equality of gender has been better established than in Russia and aimed at sharing housework with their partner. Criticizing the outsourcing of childcare to an employee, in this family model femininity is not based on housework but on women's dedication to motherhood. Other women negatively evaluated that in Germany the family model of the 'business woman' characterized by women's role as the main breadwinner of the family and the primary provider of family work has developed. These women preferred to work part-time to be able to care for their families. In this family model the responsibility of breadwinning is ascribed solely to men, while women's waged work is constructed as time devoted to women's individual needs by offering an intellectual challenge and an individual income.